Identification and expression of the Di19 gene family in response to abiotic stress in common bean (Phaseolus vulgaris L.) - Guo, Wei; Li, Xinhui; Yang, Tao; Huang, Chunguo; Zhao, Bo; Wang, Peng (Frontiers in Genetics, 2024)
Drought-induced 19 (Di19) protein plays critical biological functions in response to adversity as well as in plant growth and development. Exploring the role and mechanism of Di19 in abiotic stress responses is of great significance for improving plant tolerance. In this study, six Di19 genes were identified in the common bean (Phaseolus vulgaris L.), which were mainly derived from segmental duplications. These genes share conserved exon/intron structures and were classified into three subfamilies based on their phylogenetic relationships. The composition and arrangement of conserved motifs were consistent with their phylogenetic relationships.Many hormone-and stress-responsive elements were distributed in the promoters region of PvDi19 genes. Variations in histidine residues in the Cys2/His2 (C2H2) zinc-finger domains resulted in an atypical tertiary structure of PvDi19-5. Gene expression analysis showed rapid induction of PvDi19-1 in roots by 10% PEG treatment, and PvDi19-2 in leaves by 20% PEG treatment, respectively. Most PvDi19s exhibited insensitivity to saline-alkali stress, except for PvDi19-6, which was notably induced during later stages of treatment. The most common bean Di19 genes were inhibited or not regulated by cadmium stress, but the expression of PvDi19-6 in roots was significantly upregulated when subjected to lower concentrations of cadmium (5 mmol). Moreover, Di19s exhibited greater sensitivity to severe cold stress (6℃). These findings enhance our understanding of the role of PvDi19s in common bean abiotic stress responses and provide a basis for future genetic 字体: 倾斜 设置格式[王鹏]: 字体: 倾斜 设置格式[王鹏]: Identification and expression analysis in response to abiotic stress of Di19 gene family in common bean (Phaseolus vulgaris L.